2021
DOI: 10.3390/ijerph18041633
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Hypoxia in Endurance Training in Patients after Myocardial Infarction

Abstract: The presence of a well-developed collateral circulation in the area of the artery responsible for the infarction improves the prognosis of patients and leads to a smaller area of infarction. One of the factors influencing the formation of collateral circulation is hypoxia, which induces angiogenesis and arteriogenesis, which in turn cause the formation of new vessels. The aim of this study was to assess the effect of endurance training conducted under normobaric hypoxia in patients after myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In our own research, both in the WBV and ST groups, a decrease in the value of the resting heart rate was noted. A similar effect in relation to the standard program and modified programs was obtained by Grabara et al [ 5 ] and Nowak et al [ 31 , 37 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our own research, both in the WBV and ST groups, a decrease in the value of the resting heart rate was noted. A similar effect in relation to the standard program and modified programs was obtained by Grabara et al [ 5 ] and Nowak et al [ 31 , 37 ].…”
Section: Discussionsupporting
confidence: 83%
“…Own research has shown that both training with the use of the vibration platform (WBV) and the standard method significantly improved the MET index. A favorable increase in the value of MET associated with the conducted cardiac rehabilitation program in the second stage was often demonstrated in relation to both the standard program [ 30 ] and the modified one [ 4 , 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…The following was carried out before commencing the training program and immediately after its completion: Electrocardiographic exercise test on a treadmill (six-stage Bruce protocol: stage 1 = 2.7 km/h, 10%, stage 2 = 4.0 km/h, 12%, stage 3 = 5.5 km/h, 14%, stage 4 = 6.8 km/h, 16%, stage 5 = 8.0 km/h, 18%, stage 6 = 8.8 km/h, 20%) Exercise test using the Excalibur Sport cycle ergometer (Lode, Groningen, The Netherlands) [ 18 ]. The following were measured: test duration (min), distance covered (m), energy cost (MET), heart rate at rest and maximum (BPM), systemic blood pressure at rest and maximum (mmHg), criteria for ending the test (physiological: submaximum heart rate, i.e., 85% of HRmax determined on the basis of the following formula: 208–0.7 × age or fatigue; pathological: stenocardial pain, ST segment, and T-wave changes, rhythm and/or conduction disorders, blood pressure increase above 250/120 mmHg), maximum oxygen uptake (VO 2 max).…”
Section: Methodsmentioning
confidence: 99%
“…total cholesterol—TC (mg/dL), high-density lipoproteins—HDL (mg/dL), low-density lipoproteins—LDL (mg/dL), triglycerides—TG (mg/dL) [ 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…Traditional physical training, in line with the existing standards of management, which begins in the second stage of cardiac rehabilitation, is well known and described [1,2,3]. Few publications deal with the issue of the effectiveness of innovative forms of training in patients with diseases of the cardiovascular system [4,5,6]. The ever younger age of cardiac patients, the progress of diagnostics and the development of interventional and surgical treatment methods require the gradual introduction of various forms of physical training.…”
Section: Introductionmentioning
confidence: 99%